Capitalism, Institutional Complementarities and the Third Sector: The Private Institutions for Social Solidarity (IPSS) in Portugal - Almeida, Vasco (2008)
How can one explain the different configurations taken up, internationally, by the third sector? Why do the third sector organizations assume different logics, dynamics and functioning principles in different countries? Why do they articulate in such a diverse manner with the other sectors of the economy? This paper intends to use the theoretical contribution of the varieties of capitalism literature to provide an answer to these questions. Several studies regarding the varieties of capitalism approach have emphasized that there are various forms of capitalism, each one of them corresponding to different institutional arrangements, which bear their own logics of functioning, as well as specific institutional articulations. When considering the varieties of capitalism theoretical framework, the concept of institutional complementarities is particularly significant. It suggests that countries which develop their own particular forms of coordination in a given economic field tend to develop institutional complementarities in others sectors. In other words, the viability of an institutional form is conditioned by the existence of other different institutional forms, in a way that their conjunction offers more coherence than alternative institutional configurations. As a result, the place and role of the third sector in contemporary societies and economies should be explained through the institutional complementarities which arise from its interaction with the other mechanisms of institutional coordination, namely, State, market, hierarchies and communities. The varieties of capitalism approach and the concept of institutional complementarities can be applied to the analysis of the Portuguese third sector. Combining a quantitative and a qualitative analysis, this paper reveals that the particular configuration of the third sector in Portugal can be explained through a dynamic process that involved the constitution of institutional complementarities which were being built via established compromises between social and political forces. The analysis focuses particularly on those third sector organizations which function in the social welfare sphere - the Private Institutions for Social Solidarity (IPSS) - and shows that its characteristics and form of functioning relate themselves with the variety of capitalism existent in Portugal. The study also compares the IPSSs with their english homologues - the Charities. This reveals that their differences – related to the workforce composition by activity fields, competition level, volatility, income concentration, marketing, relations with the financial sector, and accountability - are explained by their embeddedness in different models of capitalism, generally designated as the mediterranean model and the anglo-saxon model, consolidated through a set of specific institutional complementarities.